HIV Protease Inhibitors and Insulin Sensitivity: A Systematic Review and Meta-Analysis of Randomized Controlled Trials - Kajogoo, Violet Dismas; Gorret Atim, Mary; Amare, Demeke; Geleta, Melka; Muchie, Yilkal; Tesfahunei, Hanna Amanuel; Olomi, Willyhelmina; Acam, Joan; Manyazewal, Tsegahun (Frontiers in Pharmacology, 2021)
ABSTRACT Background: Protease inhibitors (PIs) are believed to have effects on insulin sensitivity. Our main aim is to synthesize evidence and analyze PIs on insulin sensitivity, and incidences of diabetes mellitus (DM) in patients with and without HIV. Methodology: Searched PubMed, Google Scholar, ClinicalTrals.gov for randomized controlled trials (RCTs) till November 2020. Used random-effects meta-analysis model to estimate mean difference (MD), standardized mean difference (SMD) for continuous outcomes and Risk Ratio (RR) for dichotomous outcomes with Stata 14 software. Results: Identified 142 studies, and selected nine RCTs, enrolling 1,000 participants, with ages ranging from 18 to 69 years. The majority showed results that the use of PIs is linked with insulin sensitivity ie glucose disposal rates, hyperglycemia, and mean glucose uptake. The pooled analysis showed there were no significant changes in insulin sensitivity with atazanavir, whether the study is performed on healthy individuals for short terms or a long term in combination with other drugs like tenofovir or emtricitabine (SMD = 0.375, 95% confidence interval [CI] (0.035, 0.714). A atazanavir had less adverse events compared to lopinavir (RR = 0.987, 95% CI [0.849, 1.124]). Darunavir and indinavir did not demonstrate any significant changes in insulin sensitivity. Conclusions: There are significant variations in effects of PIs on insulin sensitivity. Newly diagnosed HIV patients should be investigated for DM before the start of antiretroviral therapies and routinely. RCTs should focus on sub-Sahara Africa as the region is worse affected by HIV. Keywords: HIV, protease inhibitors, insulin sensitivity, diabetes, insulin resistance, atazanavir, lopinavir/ritonavir, Darunavir.